Learning Management System for learning Al-Islam and Muhammadiyah in Indonesia: An Analysis of comparison lectures and students - Elihami Elihami (Sublim: Jurnal Pendidikan, 2022)
The research aims to provide knowledge about the recognition, and use of faculty technologies for education teachers are responsible for developing moral character. Preliminary results were gathered from a survey offered to 182 departments of four universities. The researcher used a definition and interpretation approach for qualitative use in this study. There were 530 lectures of 25-50 years of age (men and women). A study was conducted based on Kohlberg's theory's concept of gender identity findings show that technology is mostly optimistic and that universities and colleges do not have adequate technological assistance (both hardware and training). The most popular forms of technologies are course management, laptop and web applications. The data show that intermediately or marginally below, the departments as a whole operates in the accepting/use spectrum of technology. Even while the epidemic rages worldwide, closing down higher education has never been an option; instead, finding methods to avoid it has led to a growing dependence on online technologies for a course and program delivery. Although this is not intended to be a perfect alternative, some claim that online education has exacerbated the 'diploma illness' dilemma the academic and job-ready percentage